Evolution Characteristics of Microbial Diversity During the Treatment of Black-odor Water by Carbon Fiber Bio-contact Oxidation - ZHANG Min; LIU Fengru; YIN Juan; LI Hongju; XU Yang; ZHANG Yang (Renmin Zhujiang)
In order to investigate the influence of the growth environment on the evolution of the structural diversity characteristics of the bacterial community during the treatment of black-odor water by carbon fiber bio-contact oxidation,this paper studies the characteristics of bacterial community on inoculated sludge,in-equipment activated sludge and carbon fiber membrane by high-throughput sequencing techniques.The results show that with the progress of biofilm culturing,the microbial species of activated sludge in the equipment gradually decreased,the diversity of bacterial community structure increased compared with inoculated sludge.The difference in bacterial community structure between the carbon fiber membrane D sample and E sample at stable phase was small.The analysis results of dominant bacterial flora show that there were 20 phylum found in the samples.The dominant microbial populations were Proteobacteria,Pachyphyta,Actinomycetes and Bacteroides with their relative abundance of about 75%～95%.At the class level,more than 20 classes were found in the samples,the dominant microbial populations were Alphaproteobacteria,Betaproteobacteria,Deltaproteobacteria and Gammaproteobacteria.The Alphaproteobacteria and Gammaproteobacteria on activated sludge and carbon fiber in the equipment were higher than those in the inoculated sludge,and the clostridia was lower than that in the inoculated sludge,indicating that the bacterial community structure had undergone significant changes after inoculated biofilm culturing with activated sludge.